THE EFFECT OF INFLATION AND INTEREST RATE ON PROFITABILITY FOR SHARIA BANKING RESULTS - Syahril Ramadhon Alamsyah (Khatulistiwa, 2023)
This study was conducted to examine the effect of the inflation variable on the profitability of Islamic banking profit sharing in Indonesia, as well as to test whether there is an asymmetric effect of inflation and interest rate variables on the profitability of Islamic banking profit sharing in Indonesia, the study was conducted using agency theory, portfolio selection and policy. monetary. This study uses a quantitative method, the regression tool used is the Non-linear Autoregressive Lag Model (NARDL) using the Eviews 10 data processing tool, the sample of this study is Islamic banking registered with the Financial Services Authority (OJK), with an observation period from 2014 -2020. The results of this study indicate that inflation and interest rate variables have an asymmetric relationship to the profitability of Islamic banking in Indonesia, namely when inflation and interest rates rise, the effect is smaller than when inflation and interest rates fallKeywords: Profitability, Asymmetric, Inflation, Interest Rate, NARDL